Towards an environmentally and economically sustainable biorefinery: heavy metal contaminated waste wood as a low-cost feedstock in a low-cost ionic liquid process - Gschwend,FJ; Hennequin,LM; Brandt-Talbot,A; Bedoya-Lora,F; Kelsall,GH; Polizzi,K; Fennell,PS; Hallett,JP (Green Chemistry, 2020)
In the present study, we used a low-cost protic ionic liquid, 1-methylimidazolium chloride, to simultaneously fractionate heavy metal contaminated wood and extract the metals from the wood at elevated temperature and short reaction time. This treatment selectively dissolves the lignin and hemicellulose in the biomass, leaving a solid cellulose-rich pulp, while coordinating and extracting 80–100% of the metal species present in the wood in a one-pot process. The lignin stream was recovered from the liquor and the cellulose was hydrolysed and then fermented into ethanol. The ionic liquid was recycled 6 times and the metals were recovered from the liquor via electrodeposition. This is the first time that highly contaminated waste wood has been integrated into a process which does not produce a contaminated waste stream, but instead valorises the wood as a feedstock for renewable chemicals, materials and fuels, while efficiently recovering the metals, converting a toxic environmental hazard into a rich source of biorenewables. We have therefore used an otherwise problematic waste as a low-cost lignocellulsoic feedstock for a circular bioeconomy concept.